Relação entre os métodos de síntese de precursores particulados ferroicos e a obtenção de compósitos magnetoelétricos texturados - Paranhos, Rafael Rodrigo Garofalo (2015)
This study analyses the relationships between synthesis routes and physical properties of the composite system 67.5(PbMg1/3Nb2/3O3) +32.5(PbTiO3), or simply PMN-PT, as ferroelectric phase and BaFe12O19, or BaM, as magnetic phase. The choice of phases was based on the exceptional properties that both PMN-PT and BaM possess: solid solutions of the complex perovskite PMN-PT in both monocrystalline and polycrystalline forms, particularly those whose composition lies within the region of morphotropic boundary phases, have the largest known piezoelectric coefficients. BaM, or barium hexaferrite, presents relatively high property anisotropy due to its hexagonal crystal structure (expressed in particles that grow in nonequiaxed format) and easy magnetization along the c-Crystallographic axis. Thus, the main objective of this work was to obtain and characterize magnetoelectric composites (either volumetric or as two-dimensional nanostructures) textured from PMN-PT/BaM, by exploiting the quasi-piezomagnectic characteristics and the microstructural, crystallographic and magnetic anisotropyof the BaM phase. With a molar ratio of 80/20 between the ferroelectric and magnetic phases, different routes of synthesis and processing were used for the production of threedimensional ceramic composites with 0-3 connectivity, or thin films with 0-3 and 2-2 connectivity.The Pechini, sol-gel, co-precipitation,and solid state reaction techniques were applied for the synthesis of powders and/or solutions; the pressure-assisted sintering method was used for the densification of three-dimensional bodies; and the spin-coating technique was employed for the deposition of films. Physical, electrical, magnetic and magnetoelectric characterizations were performed in order to clarify the influence of the BaM phase upon composites of different configurations. In a prospective yet not exhaustive manner, relations were assessed among the experimental parameters of the various synthesis routes (with greater focus on the barium hexaferrite phase) and the production of ceramic composites of PMNPT/ BaM system. It was found that the final characteristics of the prepared materials, particularly the hysteresis behavior of the magnetoelectric coefficient as a function of applied magnetic field, were highly susceptible to variations in the morphology, size and orientation of barium hexaferrite grains, which, in turn, depended on the synthesis and sintering routes applied.